Oxidative Stress in Stem Cell Aging - Chen, Feng; Liu, Yingxia; Wong, Nai-Kei; Xiao, Jia; So, Kwok-Fai (Cell transplantation, 2017)
Stem cell aging is a process in which stem cells progressively lose their ability to self-renew or differentiate, succumb to senescence or apoptosis, and eventually become functionally depleted. Unresolved oxidative stress and concomitant oxidative damages of cellular macromolecules including nucleic acids, proteins, lipids, and carbohydrates have been recognized to contribute to stem cell aging. Excessive production of reactive oxygen species and insufficient cellular antioxidant reserves compromise cell repair and metabolic homeostasis, which serves as a mechanistic switch for a variety of aging-related pathways. Understanding the molecular trigger, regulation, and outcomes of those signaling networks is critical for developing novel therapies for aging-related diseases by targeting stem cell aging. Here we explore the key features of stem cell aging biology, with an emphasis on the roles of oxidative stress in the aging process at the molecular level. As a concept of cytoprotection of stem cells in transplantation, we also discuss how systematic enhancement of endogenous antioxidant capacity before or during graft into tissues can potentially raise the efficacy of clinical therapy. Finally, future directions for elucidating the control of oxidative stress and developing preventive/curative strategies against stem cell aging are discussed.